Performance analysis in saber - Aquili, A.; Tancredi, V.; Triossi, T.; de Sanctis, D.; Padua, E.; D'Arcangelo, G.; Melchiorri, G. (The Journal of Strength and Conditioning Research, 2013)
Fencing is a sport practiced by both men and women, which uses 3 weapons: foil, épée, and saber. In general, there are few scientific studies available in international literature; they are limited to the performance analysis of fencing bouts, yet there is nothing about saber. There are 2 kinds of competitions in the World Cup for both men and women: the "FIE GP" and "A." The aim of this study was to carry out a saber performance analysis to gain useful indicators for the definition of a performance model. In addition, it is expected to verify if it could be influenced by the type of competition and if there are differences between men and women. Sixty bouts: 33 FIE GP and 27 "A" competitions (35 men's and 25 women's saber bouts) were analyzed. The results indicated that most actions are offensive (55% for men and 49% for women); the central area of the piste is mostly used (72% for men and 67% for women); the effective fighting time is 13.6% for men and 17.1% for women, and the ratio between the action and break times is 1:6.5 for men and 1:5.1 for women. A lunge is carried out every 23.9 seconds by men and every 20 seconds by women, and a direction change is carried out every 65.3 seconds by men and every 59.7 seconds by women. The data confirm the differences between the saber and the other 2 weapons. There is no significant difference between the data of the 2 different kinds of competitions.